Comparison of decision-making skills among female football players from U-12 to professional age groups - Figueiredo Machado, Guilherme; Práxedes, Alba; González-Víllora, Sixto; Teoldo da Costa, Israel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
The aim of this study was to compare the decision-making skills of female football players of different age groups (U-12, U-14, U-16, U-18 and Professional). For this purpose, the decision-making quality and the decision-making time were measured based on the core tactical principles of the offensive and defensive phases. The sample comprised a total of 63 Spanish female football players from U-12 (n=12), U-14 (n=9), U-16 (n=15), U-18 (n=12), and professional (n=15) age groups participating in national and regional competitions for their age group. The TacticUP® platform was used to assess the decision-making skills (quality and time). The results showed no significant differences in decision-making quality (p>0.05), whereas significant differences in decision-making time were found between age groups in both offensive and defensive phases (p< 0.05). Specifically, professional players made significantly (p<0.05) quicker decisions compared to U-16 and U-12 players. Therefore, it is concluded that Spanish female football players’ decision-making skills differ between professional and youth players, although such differences are not linear.